Immediate effect of pre-made foot orthotics on variability and joint coupling patterns of rear foot and tibia during gait in male athletes with pes planus - Heydar Sadeghi; Peyman Aghaie Ataabadi; Fariborz Hovanlo (Islamic Azad University, Hamedan Branch, 2015)
Objective: The purpose of this study was to investigate the immediate effects of pre-made foot orthotics on rear-foot and tibia variability and joint coupling patterns during stance phase of gait in male athletes with pes planus. Methods: Subjects of this semi-experimental research included 8 active men with pes planus. Kinematic gait data of these subjects were recorded by a motion analysis system with 8 cameras. After calculating three-dimensional angles, vector coding method was used for assessing coupling. Shapiro-Wilk test was used to test the normal distribution of data and dependent samples t-test was used to compare means in each sub-phase. Results: Results showed that in the first 3 sub phases of stance, there were no significant differences between joint coupling with and without orthotics  (P>0.05), while in  the fourth sub-phase the mean coupling angle decreased significantly by 19% (P=0.002-P<0.05). Also, no significant difference was observed among means of joint coupling variabilities in sub phases (P>0.05).  Conclusion: These results suggest that foot orthotics does not have an effect on rear foot and tibia joint coupling patterns in the first 75 percent of stance phase of gait, but leads to a decrease in these patterns in the last 25 percent. Thus, it seems that movements of the shank decrease relative to heel movements in terminal stance phase, and this change can explain reduction in knee pain and other beneficial effects of using foot orthotics in subject with pes planus.